Estimation of college students’ ability on real analysis course using Rasch model - Isnani Isnani; Wikan Budi Utami; Purwo Susongko; Herani Tri Lestiani (REID (Research and Evaluation in Education), 2019)
This study is aimed at estimating the difficulty level of essay tests and the accuracy of students’ ability in Real Analysis essay test using the Rasch model with the QUEST program and R 3.0.3 package eRm program. The population in this study was all students of the Department of Mathematics Education, Universitas Pancasakti Tegal in the academic year 2016/2017, who were enrolled in the Real Analysis course. The data were analyzed using the R 3.0.3 package eRm program and QUEST program. The students’ ability was obtained from the result of the course final exam of the first Real Analysis course. The analysis shows that: (1) by using Rasch model for partial credit scoring, the difficulty level shows that 100% of essay questions in Real Analysis final exam is categorized as difficult, (2) the estimation of students’ ability in Real Analysis course using Rasch Model with CML method is better than the estimation of students’ ability using Rasch Model with JML approach.